Evaluation of PR3- and MPO-ANCA line and dot immunoassays in ANCA-associated vasculitis. (14th December 2020) - Kempiners, Nina; Mahrhold, Juliane; Hellmich, Bernhard; Csernok, Elena
Abstract: Objective: This study was performed to evaluate the diagnostic accuracy of novel line and dot immunoassays for detection of MPO and PR3 ANCA. Methods: Sera from 50 patients with ANCA-associated vasculitis (AAV), including granulomatosis with polyangiitis and microscopic polyangiitis, and from 45 disease controls were tested by IIF and for the presence of PR3-ANCA and MPO-ANCA by four different line or dot immunoassays, as well as by a chemiluminescence immunoassay. Results: The area under the curve of the receiver operating characteristic curve to discriminate AAV from controls was 0.858 (95% CI 0.785–0.931) for the IIF method. For the antigen-specific immunoassays, the area under the curve varied between 0.869 (95% CI 0.797–0.941) and 0.936 (95% 0.886–0.985). Conclusions: Our comparison of various ANCA detection methods showed a high degree of diagnostic precision for all of the PR3- and MPO-ANCA line and dot immunoassays investigated. The performance was equal to or better than the performance of IIF. These results indicate that novel line and dot immunoassays can serve as a first-line test method in patients with the suspected diagnosis of AAV.